HLA-G Expression Is an Independent Predictor for Improved Survival in High Grade Ovarian Carcinomas - M. J. Rutten; F. Dijk; C. D. Savci-Heijink; M. R. Buist; G. G. Kenter; M. J. van de Vijver; E. S. Jordanova (Journal of Immunology Research)
Aberrant expression of human leukocyte antigens (HLA) class I has prognostic importance in various cancers. Here, we evaluated the prognostic value of classical (A/B/C) and nonclassical (G/E) HLA expression in 169 high grade epithelial ovarian cancer samples and linked that to clinicopathological characteristics and survival. Expression of HLA-A, -B/C, or -E was not correlated with survival. Survival was prolonged when tumours expressed HLA-G (P=0.008) and HLA-G was an independent predictor for better survival (P=0.011). In addition, HLA-G expression was associated with longer progression-free survival (P=0.036) and response to chemotherapy (P=0.014). Accordingly, high expression of HLA-G mRNA was associated with prolonged disease-free survival (P=0.037) in 65 corresponding samples. Elevated serum-soluble HLA-G levels as measured by enzyme-linked immunosorbent assay in 50 matched patients were not correlated to HLA-G protein expression or gene expression nor with survival. During treatment, sHLA-G levels declined (P=0.038). In conclusion, expression of HLA-G is an independent prognostic factor for improved survival in high grade epithelial ovarian cancer and a predictor for platinum sensitivity.